Faktor Prediktor Gangguan Kognitif 30 hari Pasca Stroke Iskemik Ringan-Sedang - Rizaldy Taslim Pinzon; Carmelia Anggraini (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: There is an increasing attention on post stroke cognitive impairment. The post stroke cognitive impairment often diagnosed late. There were only few studies that measured the predictive factors for cognitive impairment post-acute ischemic stroke in Indonesia. The aim of this study is measure the predictive factors for the post stroke cognitive impairment in acute ischemic stroke.Method: This was a cohort study. The patients included were more than 18 years old, and diagnosed with acute ischemic stroke. The subjects were measured with Mini Mental State Examination (MMSE) and Clock Drawing Test (CDT) examination at day-30 at Bethesda Hospital Yogyakarta. Patients who had a history of cognitive impairment were excluded. The result of MSSE and CDT at day-30 were the outcome of this study. To determine the relationship between the independent variable and the dependent variable, it was analysed using Chi-square method followed by multivariate logistic regression. Result: A total of 140 subjects were included in the study with an average age of 62,8 years, 86 (61,4%) male and 54 (38,6%) female. Ninety-one subjects, which is 65% from total subjects, experienced post stroke cognitive impairment. The analysis of multivariate showed age greater than 70 years, education level ≤ 6 years, modified Rankin score greater than 3 at diagnosis, Barhtel Index (BI) score ≤ 4 at diagnosis, the number of multiple lesions and the location of lesion in the cortex was an independent predictor factor affecting cognitive impairment 30 days after acute ischemic stroke. Conclusion: Age greater than 70 years, education level ≤ 6 years, modified Rankin score greater than 3 at diagnosis, Barhtel Index score ≤ 4 at diagnosis, the number of multiple lesions and the location of lesion in the cortex were independent predictive factors affecting cognitive impairment 30 days after acute ischemic stroke.